IMPACT OF SPECIALTY DRUGS ON USE OF OTHER MEDICAL SERVICES - Joyce, Geoffrey F. (2008)
OBJECTIVE: To examine whether initiation of a biologic agent to treat two autoimmune disorders – rheumatoid arthritis (RA) and multiple sclerosis (MS) – affects use of other medical services. STUDY DESIGN: A longitudinal analysis from 1997 to 2005 examining linked pharmacy and medical claims from large, private employers. METHODS: The study sample included 30,761 individuals newly diagnosed with RA (92,660 person-years) and 8,961 unique individuals with MS (25,100 person-years). Negative binomial models were used to estimate changes in inpatient, outpatient and procedure use before and after initiating a biologic drug for each condition. RESULTS: Starting a biologic response modifier (BRM) was associated with a reduction in physician visits and use of expensive procedures for patients with RA within two to three years of initiation. Use of immunomodulatory therapy for MS was associated with a reduced number of hospitalizations and expensive procedures within two years of initiation. While biologics may reduce other types of service use, the savings do not come close to offsetting the full cost of these drugs. CONCLUSIONS: Given the high cost of many specialty drugs, health plans may rightly focus on making sure only patients who will most benefit receive them. But once such patients are identified, it makes little sense to limit coverage.